A forced‐choice preferential looking task for the assessment of vision in dogs: pilot study. (25th November 2018) - Graham, K. L.; Byosiere, S.‐E.; Feng, L. C.; Sanders, M.; Bennett, P. C.; Caruso, K.; McCowan, C. I.; White, A.
Abstract : Objectives: To describe preliminary use of a forced‐choice preferential looking task for the clinical assessment of vision in dogs. Materials and Methods: The vision of 18 pet dogs was investigated in two separate studies using a forced‐choice preferential looking task: multiple observers watched eye, head and body movements on video recordings to identify cues suggesting when a dog had seen the feature of interest. Human observer reliability was determined using eight dogs and computer‐generated stimuli. Visual acuity was assessed using computer‐generated grating stimuli: in real‐time, an observer watched each dog's eye movement patterns and behaviour to decide whether each grating was seen. Stimuli were presented in a step‐wise manner and were controlled by the observer. Acuity was estimated as the highest spatial frequency the dog was determined to have seen. Results: Median estimated visual acuity was better at 1 m compared to that at 3 m. Average test time was longer at a 3‐m distance than at 1 m. Inter‐ and intra‐observer reliability was better from 1 m than from 3 m. Clinical Significance: Preliminary use of a forced‐choice preferential looking task for measurement of visual acuity in dogs has potential use as a clinical tool for the assessment of vision in dogs.